Molecular diagnostic test systems for meat identification: A comparison study of the MEAT 5.0 LCD-Array and innuDETECT Assay detection methods - Golian, Jozef; Benešová, Lucia; Drdolová, Zuzana; Semjon, Boris; Martišová, Patrícia; Kozelová, Dagmar (Acta veterinaria Brno, 2020)
The aim of the study was to compare the efficiency, sensitivity and reliability of the MEAT 5.0 LCD-Array and innuDETECT Assay detection kits in identifying selected animal species. Samples were taken from the femoral muscles of six animal species (turkey, chicken, cattle, pig, sheep and goat), and six variants of binary meat mixtures were analysed at 18 different concentration levels of addition. The MEAT 5.0 LCD-Array test was able to detect 0.1% of other meat additions in two meat mixtures and 0.5% in four meat mixtures. The innuDETECT Assays were able to detect the addition of 0.1% of other meat in three meat mixtures, 0.5% in two mixtures and 1% in one meat mixture. Subsequently, these methods were applied in practice to 136 samples of various products taken from commercial food networks. By performing extensive monitoring, we identified 60 products in which one to three species were detected besides what was present on the product label. Nine products were contaminated with pig DNA. Two products that the MEAT 5.0 LCD-Array kit identified as positive for the presence of pig DNA were not confirmed by the innuDETECT Pork Assay kit. We recommend these methods of analysis to comprehensively monitor the presence of animal species in food samples, regardless of the degree of heat treatment or mechanical processing, as a tool to detect food adulteration.